Edukasi Pencegahan Perilaku Cyberbullying pada Siswa Sekolah Menengah Kejuruan - Siti Rofiah; Noor Yunida Triana; Murniati Murniati (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Social media and information technology advancements have facilitated communication and information sharing, but they have also had unfavorable effects, such as an increase in teenage cyberbullying. Cyberbullying is bullying conduct that occurs online, including threats, defamation, and insults. Teenagers' psychological health is impacted by these phenomena, which lowers academic achievement and causes stress, anxiety, and sadness. Objective: The goal of this community service program is to raise students' awareness of cyberbullying by educating 57 Visual Communication Design (DKV) majors in grades X, XI, and XII. Method: This community service approach uses PowerPoint presentations and pocket booklets for lectures and conversations, along with pretest and posttest questions about cyberbullying. Result: Prior to the training, the cyberbullying education findings indicated that 59.65% of students fell into the poor group, 22.80% into the sufficient category, and 17.54% into the good category. Following the training, the posttest results revealed a decrease in the other two categories and a rise of 92.98% in the good category. Conclusion: In conclusion, this community service activity indicated that educational sessions using lecture and discussion methods, supported by appropriate media, facilitated participants’ understanding and engagement with the topic